2016
DOI: 10.3847/0004-637x/818/1/32
|View full text |Cite
|
Sign up to set email alerts
|

The Spectral Amplitude of Stellar Convection and Its Scaling in the High-Rayleigh-Number Regime

Abstract: Convection plays a central role in the dynamics of any stellar interior, and yet its operation remains largely hidden from direct observation. As a result, much of our understanding concerning stellar convection necessarily derives from theoretical and computational models. The Sun is, however, exceptional in that regard. The wealth of observational data afforded by its proximity provides a unique test bed for comparing convection models against observations. When such comparisons are carried out, surprising i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 38 publications
3
103
4
Order By: Relevance
“…As a result, the entropy difference between the top boundary and the bulk of the domain ∆ s ≡ |max s − min s | increases as Pr increases. However, Pr-dependence of the upper boundary layer is small compared with the previous studies (O 'Mara et al 2016), having no scaling relations between the thermal diffusivity κ, the thickness of the thermal boundary layer d t , and the entropy difference ∆ s , such as d t ∝ κ 1/2 or ∆ s ∝ κ −1/2 which can only hold for simulations imposing a diffusion-type upper boundary condition where the energy flux is released through the thermal conduction term (Featherstone & Hindman 2016).…”
Section: Isotropic Thermal Diffusionmentioning
confidence: 92%
See 2 more Smart Citations
“…As a result, the entropy difference between the top boundary and the bulk of the domain ∆ s ≡ |max s − min s | increases as Pr increases. However, Pr-dependence of the upper boundary layer is small compared with the previous studies (O 'Mara et al 2016), having no scaling relations between the thermal diffusivity κ, the thickness of the thermal boundary layer d t , and the entropy difference ∆ s , such as d t ∝ κ 1/2 or ∆ s ∝ κ −1/2 which can only hold for simulations imposing a diffusion-type upper boundary condition where the energy flux is released through the thermal conduction term (Featherstone & Hindman 2016).…”
Section: Isotropic Thermal Diffusionmentioning
confidence: 92%
“…For example, since we impose large viscous and thermal SGS diffusivities with the typical Reynolds number Re eff calculated as 30−40, the parameter regime studied in our simulations is laminar. It is expected that, if SGS ν is decreased and the Reynolds number Re (and thus Rayleigh number Ra) increases, the thermal effect would become ineffective and v rms would cease to diminish being independent of the values of diffusivities (Featherstone & Hindman 2016).…”
Section: Implications For Solar Convectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been partially confirmed by Hotta et al (2015), who have discussed the possible role of small-scale magnetic fields in suppressing the formation of large-scale flows. Furthermore, Featherstone & Hindman (2016) have found that with increasing Rayleigh numbers, there is more kinetic energy at small scales and less at large scales such that the total kinetic energy is unchanged by this rearrangement of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Greer et al 2015) or smaller (e.g. Featherstone & Hindman 2016) than those at the surface. If most of the kinetic energy were to reside on small scales throughout the convection zone even at a depth of several tens of megameters and beneath, E(k) is expected to decrease toward smaller wavenumbers k either like white noise ∝ k 2 or maybe even with a Batchelor spectrum ∝ k 4 (Davidson 2004).…”
Section: Introductionmentioning
confidence: 99%